2018
DOI: 10.3389/fenrg.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating the SWOT Analysis of Marine Renewable Energies

Abstract: Energy transitions require strategic plans that minimize inefficiencies and maximize energy production in a sustainable way. This aspect is fundamental in the case of innovative technologies based on marine renewable energies. Marine renewable energies involve problems and advantages which imply a reconceptualization of marine space and its management. Through an holistic SWOT analysis the main strengths, weaknesses, opportunities and threats are highlighted in this paper, considering social, economic, legal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This value is much lower (i.e., 94%) than the CIE of current Italian electricity mix. The potential reduced CO 2 emission due to the deployment of marine renewable energy for the electricity production have been considered as an "opportunity" for the blue energy technology development within a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis regarding the deployment of Marine Energy in the Mediterranean Area carried out by Goffetti et al (2018). Threats have been highlighted in economic and legal aspects that slow down the implementation of blue energy technologies coupled with lack of economic incentives (Goffetti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This value is much lower (i.e., 94%) than the CIE of current Italian electricity mix. The potential reduced CO 2 emission due to the deployment of marine renewable energy for the electricity production have been considered as an "opportunity" for the blue energy technology development within a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis regarding the deployment of Marine Energy in the Mediterranean Area carried out by Goffetti et al (2018). Threats have been highlighted in economic and legal aspects that slow down the implementation of blue energy technologies coupled with lack of economic incentives (Goffetti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy for example, the lack of social acceptance for offshore constructions can result in project rejections or costly delays (Pisacane et al, 2018). Another study in Italy revealed that the local society was in favor of onshore renewables, such as photovoltaics and wind farms, but against offshore renewables (Goffetti et al, 2018). In Cyprus, social acceptance for implementing the Orites onshore wind Farm was encouraging but it may not be the same when it comes to offshore constructions near touristic infrastructure (Fokaides et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, the procedures are very complicated and time consuming due to the large number of public services having jurisdiction in the sea (MAESTRALE Project, 2018). Goffetti et al (2018) have characterized the current permitting procedures and existing gaps in the Italian law as a weakness and threat. In addition, according to European Marine Spatial Planning (https://www.msp-platform.…”
Section: Discussionmentioning
confidence: 99%
“…The SWOT analysis has long been used as an instrument for strategic and policy planning in economic settings but has recently also been applied as a strategic planning aid in other sectors (Goffetti et al 2018). It is a strategic analysis tool focussed on achieving change and can be utilised to help understand complex predefined concepts while focussing on identifying changes and strategies which improve the concept.…”
Section: Swot Analysismentioning
confidence: 99%
“…It allows for a better structured qualitative analysis of concepts over the traditional discourse analysis and promotes a multidimensional analysis compared to the more economically focussed cost-benefit analysis (Fertel et al 2013). Recent more novel applications include the analysis of energy policy (Fertel et al 2013) and the marine renewables sector in Italy (Goffetti et al 2018), as well as the rigs-to-reefs decommissioning strategy for offshore structures (Smyth et al 2015), with a focus on identifying avenues for possible sustainable change.…”
Section: Swot Analysismentioning
confidence: 99%